PEMANFAATAN TEKNOLOGI PASANG SURUT DALAM BUDIDAYA IKAN DAN SAYURAN DI DAYAH ISTIQAMATUDDIN RAUDHATUL MU'ARRIF: STRATEGI KETAHANAN PANGAN - Cut Dara Dewi; Ismarica Ismarica; Ika Rezvani Aprita (Universitas Mataram, 2026)
Dayah Istiqamatuddin Raudhatul Mu’arrif is a traditional Islamic educational institution located in Dusun Alue Seuneuhi, Gampong Neuheun, Aceh Besar, which faces financial constraints and owns 4,500 m² of land, with approximately 1,500 m² remaining underutilized. This condition was addressed through the development of an integrated aquaculture–agriculture system using tidal technology as a strategic effort to enhance food security, reduce costs, and strengthen students’ practical skills. The community service program aimed to improve food self-sufficiency, promote the economic independence of the dayah, and equip students with practical competencies to support self-reliant and productive livelihoods. The implementation method included training and mentoring in fish and vegetable farming, with stages covering site survey, socialization, construction of tidal ponds, vegetable planting, catfish stocking, mentoring, and initial evaluation. The results demonstrated significant improvement in students’ understanding and skills related to tidal technology application in aquaculture. Active participation during training also fostered greater awareness of the importance of modern technology in aquaculture development. The evaluation results indicated that prior to the program, 18.75% of the students demonstrated a moderate level of understanding. Following the socialization and training activities, a substantial improvement was observed, with 85% of the students achieving a high level of comprehension. Overall, this program has strong potential to empower students by enhancing their knowledge and skills in innovative aquaculture practices, thereby creating opportunities for productive entrepreneurship that supports economic growth and community welfare.